Protein C and protein S deficiency associated cerebral venous thrombosis: one case report. - HUANG Zhan; ZHU Ming-fang; MENG Qi; TAN Lei-lei; ZHANG Jie-wen; HUANG Yue (Chinese Journal of Contemporary Neurology & Neurosurgery, 2025)
Objective To report one case with protein C deficiency (PCD) and protein S deficiency (PSD) associated cerebral venous thrombosis (CVT), and to explore diagnostic and therapeutic strategies. Methods and Results A 27-year-old male patient presented with positional headache, worsened in supine position and relieved upon standing. Imaging findings showed thrombosis in the right transverse sinus, sigmoid sinus, and confluence of sinus. Laboratory tests showed significantly reduced protein C and protein S activities (49% and 51%) and elevated cerebrospinal fluid (CSF) pressure (> 330 mm H2O). Genetic test identified a frameshift mutation in the PROC gene [c.574_577del (p.Val192Serfs*5)] and missense mutation in the PROS1 gene [c.1915T > G (p.Cys639Gly) and c.301C > T (p.Arg101Cys)]. After receiving heparin followed by non-vitamin K oral anticoagulants (NOACs), alongside intracranial pressure reduction, neurotrophic therapy, and analgesia treatment, the patient's headache symptom resolved, and at 4-month follow-up reexamination showed CSF pressure normalized (135 mm H2O), with protein C and protein S activities rising to 53% and 54.10% (still below normal ranges). No headache recurrence was observed. Conclusions PCD and PSD are critical etiological factors for CVT. NOACs effectively improve venous reflux and avoid warfarin-related coagulation dysfunction, representing a preferred therapeutic option. Screening for coagulation protein activity and genetic analysis in young patients is essential to guide precise anticoagulation management.